Endurance anemia, relevance to triathlon - Cairo, G. (Triathlon Medicine, 2019)
Since anemia limits the delivery of oxygen to exercising muscle, avoiding anemia is essential for triathletes to maintain or improve athletic performance. However, exercise-associated conditions, such as iron deficiency, hypoxia, and inflammation, can often be pathogenetically linked to sports anemia. This chapter summarizes recent advances showing the relevance of anemia for physical exercise and athletic performance. In particular, the alterations in the control of iron homeostasis and the relevance of iron-deficient anemia to sports physiology are described.